Transformation of Mosques in Building the Community's Economy: Contribution to Community Empowerment - Ahmad, Ahmad Prawira; Abu, Abu Bakar Siddik (Alhamdulillah : Jurnal Agama Islam, 2024)
This study aims to analyze the role of mosques in empowering the community's economy through programs that are held, such as entrepreneurship training and zakat management. The results of the study indicate that mosques have significant potential in improving community welfare by opening business opportunities and increasing community income. However, there are challenges in terms of human resource management and limited access to capital that hinder the effectiveness of the program. Therefore, collaboration between mosques, Islamic financial institutions, the government, and the private sector is needed to overcome these obstacles and strengthen the positive impact of economic empowerment programs in mosques. This study also recommends developing the capacity of mosque managers and increasing congregation participation in economic programs as important steps to achieve sustainability and success of community economic empowerment.